Coronary Artery Perforation: Insights and Outcomes From a 13-Year Experience at a District General Hospital - Ibrahim Antoun; Navid Munir; Falik Sher; Mueed Akram; Julia Baron; Kamal Chitkara; Manoj Bhandari (Journal of Interventional Cardiology)
Conclusion: CAP remains a rare, potentially lethal complication of PCI in a DGH setting, with an incidence, pattern and treatments similar to those of high-volume PCI teaching centres. Early recognition and proper management are crucial.